Integrated Marketing Strategy on Original Auto Parts E-Commerce Platform: a Case Study of Partgenie on Developing B2C and B2B Markets - Syafia Nurmala; Rhian Indradewa; Dimas Angga Negoro; Mira Kartika Dewi Djunaedi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The growth of e-commerce platforms in the automotive sector is accompanied by the rampant circulation of counterfeit parts, so consumer trust is a crucial factor for business success. This study aims to comprehensively describe and analyze the marketing strategy of PartGenie, an original car spare parts e-commerce platform that serves the business to consumer (B2C) and business to business (B2B) segments, including segmentation, targeting, and positioning (STP) strategies, marketing mix implementation, as well as sales strategies and revenue projections. The research uses a descriptive qualitative approach with a case study design, sourced from primary data in the form of PartGenie business plan documents and secondary data from literature studies, analyzed through data reduction, data presentation, and conclusion drawn. The results show that PartGenie formulates segmentation based on demographic, geographical, and behavioral dimensions, with positioning that highlights the guarantee of product authenticity and platform convenience through the tagline